Students' perceptions on conducting a real-life conversation outside the campus via the outcome-based education system / Jenny @ Janey Mosikon, Bernadette P. Lidadun and Delia L. Olaybal - Mosikon, Jenny @ Janey; Lidadun, Bernadette P.; Olaybal, Delia L. (Research Management Institute (RMI), 2012)
Driven by the principles of Outcome-Based Education (OBE), this research focuses on students' perceptions on their experiences in a project of video-taping themselves while 'making and responding to enquiries' in the real-life conversation outside the campus. After being taught the conversational skills of making and responding to enquiries (BEL 120 Syllabus) and doing role-play to practice these skills, two groups of thirty students were asked to conduct the project in which they video-taped their conversations in real-life situations such as the shopping malls, tourist information centres, fast food outlets and hotels using the acquired skills. The video recordings were analysed and the learners were interviewed to find out their perceptions and experiences in demonstrating the conversational skills of making and responding to enquiries in real-life situations. Data were collected qualitatively in the form of students' narratives of their perceptions and experiences before, during and after the project. The findings highlighted how video-recording of students' reallife conversations outside the campus could be used as a learning tool as well as an assessment method for teachers, as the project not only involves multiple skills in planning, executing and producing the end product but also most importantly, it is an observable demonstration of the students' learning after having learnt the skills in the classroom. This paper is expected to aid teachers and syllabus designers in focusing on Outcome-Based Education which stresses on the facilitation of the desired outcomes.